AN ANALYSIS OF THE HYDRODYNAMIC REGULARITIES OF DEEP STRATIFIED SYSTEMS - Vsevolozhskiy V.A.; Dyunin V.I. (My University, 1996)
The problem of the hydrodynamics of the deep horizons of platforms was examined with reference to research described in the literature carried out in various parts of Russia. An analysis of the distribution of the hydrodynamic potentials in deep stratified systems, the results of the solution of hydrodynamic problems and the production of a general balance equation for isolated blocks formed the basis of several calculations about the formation and movement of water in deep stratified complexes.